Comparative Study on Efficacy of Ketorolac and Pethidine for Postoperative Pain Management - Shrestha, Laxmi; Joshi, Bishal; Palikhey, Anjan; Bhattarai, Kushal (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Postoperative pain management is essential for early mobilization and rehabilitation to enhance recovery and to reduce morbidity. Ketorolac and pethidine are two most common analgesics used in the postoperative setting for pain management. MATERIAL AND METHODS: Sixty patients (n=60) of age group 18-60 years who undergone various surgical procedures were divided randomly into two groups (T1 and T2). T1 group received inj. ketorolac 5 mg/kg IM and T2 group received pethidine 1.5 mg/kg IM body weight respectively on 6 hourly basis for 48 hours postoperatively. Patients were assessed in the recovery room for pain according to Visual Analogue Scale (VAS), Verbal Rating Scale (VRS) and Sedation Score after 1, 6, 12, 18, 24 and 48 hours of drug administration. Analgesic efficacy was measured using VAS and VRS. Safety of the drugs was assessed by using Sedation Score. RESULTS: Ketorolac showed equianalgesic effect as pethidine estimated by VAS score at 18th and 48th hour. In other periods of observation, pethidine exhibited better analgesic effects than ketorolac. However, ketorolac shows less incidence of sedation compared to pethidine. CONCLUSION: This study showed that postoperative pain during the first 48 hours can be relieved by either ketorolac or pethidine. Ketorolac appeared safer than pethidine while pethidine appeared more effective analgesic than ketorolac in the management of postoperative pain.